Active commuting is associated with a lower risk of obesity, diabetes and metabolic syndrome in Chilean adults. (28th July 2017) - Steell, Lewis; Garrido-Méndez, Alex; Petermann, Fanny; Díaz-Martínez, Ximena; Martínez, María Adela; Leiva, Ana María; Salas-Bravo, Carlos; Alvarez, Cristian; Ramirez-Campillo, Rodrigo; Cristi-Montero, Carlos; Rodríguez, Fernando; Poblete-Valderrama, Felipe; et al.
Abstract: Background: There is limited evidence on how active commuting is associated with health benefits in developing countries. The aim of this study therefore was to investigate the associations between active commuting and markers of adiposity and cardiometabolic risk in the Chilean adult population. Methods: In total, 5157 participants from the Chilean National Health Survey 2009–10 were included in this cross-sectional study. Active commuting was measured using the Global Physical Activity Questionnaire (GPAQ v2). Body mass index (BMI) and waist circumference (WC) were measured and used to define obesity and central obesity. Type 2 diabetes (T2D) and metabolic syndrome were determined using WHO and updated ATPIII-NCEP criteria, respectively. Results: The main finding of this study is that a 30 min increase in active commuting is associated with lower odds for BMI > 25.0 kg m −2 (0.93 [95% CI: 0.88–0.98, P = 0.010]). Similarly, the odds for central obesity was 0.87 [0.82–0.92, P < 0.0001]. Similar associations were found for T2D (0.81 [0.75–0.88], P < 0.0001) and metabolic syndrome (OR: 0.86 [0.80–0.92], P < 0.0001). Conclusion: Our findings show that active commuting is associated with lower adiposity and a healthier metabolic profile including lower risk for obesity, diabetes and metabolic syndrome.